2017
DOI: 10.1016/j.mce.2016.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of bovine ovarian follicular and luteal cells provides insight into cellular identities and functions

Abstract: After ovulation, somatic cells of the ovarian follicle (theca and granulosa cells) become the small and large luteal cells of the corpus luteum. Aside from known cell type-specific receptors and steroidogenic enzymes, little is known about the differences in the gene expression profiles of these four cell types. Analysis of the RNA present in each bovine cell type using Affymetrix microarrays yielded new cell-specific genetic markers, functional insight into the behavior of each cell type via Gene Ontology Ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…It was therefore hypothesized that the upregulation may be associated with the angiogenesis of the CL. A further study conducted by Romereim et al ( 38 ) demonstrated that the CCNl/Cyr61 gene is highly expressed in small luteal cells isolated from cows. These findings support the hypothesis that CCNl/Cyr61 is important in the development of the CL.…”
Section: Ccn1/cyr61 and The Female Reproductive Systemmentioning
confidence: 93%
“…It was therefore hypothesized that the upregulation may be associated with the angiogenesis of the CL. A further study conducted by Romereim et al ( 38 ) demonstrated that the CCNl/Cyr61 gene is highly expressed in small luteal cells isolated from cows. These findings support the hypothesis that CCNl/Cyr61 is important in the development of the CL.…”
Section: Ccn1/cyr61 and The Female Reproductive Systemmentioning
confidence: 93%
“…representation of components of the IL-33 receptor complex (Romereim et al, 2017;Talbott et al, 2017). In the regressing CL, IL-33 could play a role in macrophage recruitment (Carlock et al, 2014; Wu et al, 2015) and mast cell activation (Lott et al, 2015); and is likely derived from the endothelial cells rather than the steroidogenic cells of the CL (Carlock et al, 2014).…”
Section: Cytokine Signalingmentioning
confidence: 99%
“…Previous studies and our investigations showed that the NR5A2 , STAR , FGF2 and BMP5 genes might have potential application value in regulating caprine oestrus. Furthermore, we identified cell-type makers and potential lineage markers in follicular development that showed different methylation levels; these markers included cadherin-12 ( CDH12 ), regulators of G-protein signalling ( RGSs ) and NIPA-like protein 3 ( NIPAL3 ) [ 57 ]. In addition, several regions (chromosomes 5 and 17) associated with the same gene or gene cluster ( DGCR6L , HOXC4 , HOXC5 , HOXC6 , HOXC8 , HOXC9 and HOXC10 ) can be differentially methylated (Additional file 4 : Table S4).…”
Section: Discussionmentioning
confidence: 99%